Model Digitalisasi Kinerja Sumber Daya Manusia Dengan Menggunakan Pendekatan Strategis yang Berorientasi pada Pelayanan di Perusahaan Umum Daerah Tirtawening Kota Bandung - Kartini, Sari; Narimawati, Umi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The research aims at understanding the role of EHRM as an effort to improve the service performance of the Tirtawening regional public company. In this research, the author applies research with a qualitative approach, and a case study method with interview techniques and the use of secondary data. The data were analyzed using descriptive and analytical techniques and SWOT. The findings of the research are as follows: 1) The EHRM model used contains elements of HR policies and strategies, environmental factors, and E HRM outputs, 2) HR skill barriers that need to be adjusted to the implementation of EHRM, adjustments to supporting infrastructure and implementation of eHRM in implementing it into customer service, 3) EHRM has implications for improving the performance of excellent service to customers